Yamaguchi Syndrome – a pseudoacute coronary syndrome of the Young: a case report on apical hypertrophic cardiomyopathy - Alvin Oliver Payus; Farisha Mohd Sholeh; Norlaila Mustafa (Wolters Kluwer - Medknow, 2019)
Yamaguchi syndrome, or apical hypertrophic cardiomyopathy (ApHCM), is a nonobstructive subtype of hypertrophic cardiomyopathy which predominantly affects the left ventricular apex. Due to the nature of its presentation that mimics acute coronary syndrome and also to the unfamiliarity of the condition by some physicians, the diagnosis of ApHCM is frequently missed or delayed. Here, we report a case of a young male who presented with chest pain and breathlessness. His cardiac enzyme was normal and electrocardiogram showed giant negative T-waves. He was treated as unstable angina and was then subjected to a line of diagnostic procedures including coronary angiogram before he subsequently underwent ventriculogram which reveal a characteristic “spade-like” configuration over the left ventricle, in keeping with the diagnosis of ApHCM. The purpose of this case report is to emphasize the importance of keeping ApHCM as one of the differential diagnoses in a young patient presented with chest pain.